2020
DOI: 10.1111/trf.15916
|View full text |Cite
|
Sign up to set email alerts
|

Validation of PLASMIC score: an academic medical center case series (2012‐present)

Abstract: BACKGROUNDThe PLASMIC score is a rapid and inexpensive tool for predicting severe ADAMTS13 deficiency (activity <10%) in patients with suspected thrombotic thrombocytopenic purpura (TTP) by analyzing seven parameters (platelet count; combined hemolysis variable; absence of active neoplasia; absence of an organ or stem‐cell transplant; mean corpuscular value; international normalized ratio; and serum creatinine). The purpose of this study was to validate the PLASMIC score at a large multi‐institutional acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Median ADAMTS13 activity was 5% (3%–6%) with a median inhibitor value of 2.4 BU (0.7–10) in 17 individuals. Median PLASMIC and FRENCH clinical prediction scores used to stratify risk for TTP were 6.5 and 2.5, respectively, falling into high‐risk category for these prediction scores 19,20 . See Table 1 for presenting labs on admission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median ADAMTS13 activity was 5% (3%–6%) with a median inhibitor value of 2.4 BU (0.7–10) in 17 individuals. Median PLASMIC and FRENCH clinical prediction scores used to stratify risk for TTP were 6.5 and 2.5, respectively, falling into high‐risk category for these prediction scores 19,20 . See Table 1 for presenting labs on admission.…”
Section: Resultsmentioning
confidence: 99%
“…All patients presented with thrombocytopenia and microangiopathic hemolytic anemia on initial presentation with a median platelet count of 17 × 10 9 /L, hemoglobin 6.8 g/dl (4.6-113.9), and LDH 1940 U/L (380-11,363). Median ADAMTS13 activity was 5% (3%-6%) with a median inhibitor value of 2.4 BU (0.7-10) in 17 individuals.Median PLASMIC and FRENCH clinical prediction scores used to stratify risk for TTP were 6.5 and 2.5, respectively, falling into high-risk category for these prediction scores 19,20. See Table1for presenting labs on admission.When analyzing all TTP episodes (n = 28) in 18 patients, neurologic and renal symptoms were seen in an equal percentage (n = 21; 77%).…”
mentioning
confidence: 99%
“…Bendapudi et al created the PLASMIC score using two cohorts with a high prevalence of TTP (14 to 47%) and demonstrated its accuracy for TTP diagnosis (AUC 0.91-0.96) (10). Further studies with a high TTP prevalence (25 to 70%) confirmed the good diagnostic value of both the PLASMIC and French scores (23)(24)(25)(26)(27)(28)(29). However, they also included highly selected patients recruited among those that had ADAMTS13 measurement (30).…”
Section: Discussionmentioning
confidence: 99%
“…Classic HUS is an infection‐related TMA often associated with Escherichia coli 0104:4 that responds to supportive care. Some classic HUS patients may require dialysis as part of the supportive care, but TPE has not been found to improve the outcome [22]. The mortality rate of the combined group of aHUS and HUS was similar to those in the TTP group and primarily treated with supportive care (after the initial TPE treatment before TTP was ruled out).…”
Section: Discussionmentioning
confidence: 99%
“…At the time of publication of the first research evaluating the PLASMIC score, few institutions were testing for ADAMTS-13 in-house. Therefore, the PLASMIC score had more utility in the setting of evaluating a patient within the first few days after presenting with signs/ symptoms of TMA/TTP without the availability of rapid ADAMTS-13 activity results [20][21][22][23]. In this study, we evaluated our 14-year experience of patients referred to the apheresis service with the clinical suspicion of TTP.…”
Section: Introductionmentioning
confidence: 99%